The Benefits Of Being Shy - Apprich, Fran (European Scientific Journal, ESJ, 2017)
â€œShy people notice everything but they do not get noticedâ€ (Author unknown) Practicing shyness and modesty should be an integral part of the managerial education yet it often gets associated with weakness. Anyone who has ever experienced a shy, modest and kind line manager feels a sense of ease and approachability so alien to nowadays business world and backstabbing mentality. Shy and modest managers see the person behind the employee rather than the employee as a number. Today's business world is lacking a portal for shyness and modesty among line managers who have grown in numbers but not very often human quality in recent years. For this reason, it is important that researchers, educators, managers and businesses become aware of the nature of shyness and modesty and its benefits. Researchers are in a unique position to help businesses and institutions reflect upon and understand that aggressive behavior can potentially harm the progress and image of a company rather than insuring to build a successful team, honest service and lasting product.